Accuracy of robotic coil positioning during transcranial magnetic stimulation. (17th September 2019) - Goetz, Stefan M; Kozyrkov, I Cassie; Luber, Bruce; Lisanby, Sarah H; Murphy, David L K; Grill, Warren M; Peterchev, Angel V
Abstract: Objective . Robotic positioning systems for transcranial magnetic stimulation (TMS) promise improved accuracy and stability of coil placement, but there is limited data on their performance. Investigate the usability, accuracy, and limitations of robotic coil placement with a commercial system, ANT Neuro, in a TMS study. Approach . 21 subjects underwent a total of 79 TMS sessions corresponding to 160 hours under robotic coil control. Coil position and orientation were monitored concurrently through an additional neuronavigation system. Main results . Robot setup took on average 14.5 min. The robot achieved low position and orientation error with median 3.54 mm (overall, 1.34 mm without coil–head spacing) and 3.48°. The error increased over time at a rate of 0.4%/minute for both position and orientation. Significance . Robotic TMS systems can provide accurate and stable coil position and orientation in long TMS sessions. Lack of pressure feedback and of manual adjustment of all coil degrees of freedom were limitations of this robotic system.